Book Review: Introduction to Philosophy - Sirithanyaporn, Suchaya; Sudachan, Supatharn; Sirisawad, Pinyo (Mahachula Academic Journal, 2026)
This book review critically examines Introduction to Philosophy, written by faculty members of Mahachulalongkornrajavidyalaya University, with particular attention to its content, structure, presentation, and educational value. The book consists of seven chapters covering an introduction to philosophy, principles and methods of reasoning, truth, knowledge, goodness, beauty, and the development of philosophy. The review finds that one of the book’s major strengths lies in its systematic organization of philosophical knowledge from fundamental concepts to major philosophical questions. It begins with the meaning, origins, branches, and value of philosophy, proceeds to principles of reasoning, and subsequently explores fundamental human questions concerning truth, knowledge, goodness, and beauty, before concluding with the historical development of Western and Eastern philosophy. This structure encourages students not only to acquire philosophical knowledge but also to question assumptions, examine arguments, evaluate beliefs, and seek answers through reasoned inquiry. Another notable strength is the inclusion of both Western and Eastern philosophical traditions, together with Buddhist philosophical perspectives, enabling readers to appreciate diverse approaches to truth and human understanding. Nevertheless, because the book covers a broad range of topics and contains substantial philosophical terminology, beginning students may benefit from additional contemporary examples, diagrams, comparative tables, and practical exercises to make abstract philosophical concepts more accessible. The principal insight emerging from this review is that philosophy should not be understood merely as a collection of answers, but as a process through which human beings learn to question, reason, examine knowledge, and reflect upon the values of life. The book is therefore valuable not only as an introductory philosophy textbook but also as an intellectual instrument for cultivating critical and reflective thinking among university students and general readers.